El método de aprendizaje cooperativo en el desarrollo de la comprensión lectora (reading) en los estudiantes de décimo año de la Unidad Educativa “Vicente Anda Aguirre” en el período académico 2015–2016. - Silvia Yumbillo Sánchez, Silvia (2017)
The research entitled: The cooperative learning method in the development of reading comprehension in the students of the Ten Year of the Vicente Anda Aguirre Educational Unit in the academic period 2015-2016, has the objective of orienting the students The application of active strategies with the aim of improving the reading comprehension of different texts in English, whose structure was focused on the philosophical, epistemological, pedagogical, psychological, sociological, axiological and legal basis. The theoretical framework is structured with themes and sub-themes related to the independent variable that is the method of cooperative learning and the dependent variable is the development of reading comprehension. The methodology was based on a quasi-experimental design and applied because the proposal is executed based on the reading strategies such as the jigsaw, think-pair-share and graphic organizers, the types of research correspond to a causal descriptive-explanatory process of Field and bibliographic. The method applied is hypothetic-deductive and descriptive. The technique used was observation, supported by a practical instrument that is the observation sheet based on evaluation indicators and with a defined population that is the students of the Tenth Year of Basic Education of the Vicente Anda Aguirre Educational Unit. Within the exhibition and discussion of results, the data obtained through the observation sheet were processed to be tabulated and organized into tables and statistical graphs with their respective percentages, and then proceed to the verification of the 3 specific hypotheses; The alternative guidelines correspond to the proposal of Reading Together is Better where activities are carried out with reading strategies that allow the reading comprehension of the students. As a result, of the progress there is a better understanding of texts in English, but principally participating with responsibility in group work, reading individually and collectively, paying attention and concentration to identify the main idea as secondary ideas of the text, identify the meaning of new terms about the reading in context, support their partners with their knowledge to improve their learning, share defined and real knowledge to achieve a common goal is to achieve a better level of their vocabulary and read fluently to understanding The relevant information.